2020
DOI: 10.12700/aph.17.3.2020.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Ranking and Assessment of the Efficiency of Social Media using the Fuzzy AHP-Z Number Model - Fuzzy MABAC

Abstract: Methods of ranking and evaluation of the effectiveness of Social Media (SM) given and applied in this paper are the basis for the selection of online media that the public administration uses when communicating with citizens. The methodology presented is based on multicircular decision-making using the Fuzzy Analytical Hierarchical Process (fuzzy AHP) -Z number model -Fuzzy Multi-Attributive Border Approximation Area Comparison (fuzzy MABAC), which eliminates the traditional intuitive ratings of PR services.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…[65]. In most cases, the authors perform a sensitivity analysis based on the changes in weight coefficients of criteria [66][67][68][69][70][71][72][73][74][75][76], as is the case in this paper as well.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…[65]. In most cases, the authors perform a sensitivity analysis based on the changes in weight coefficients of criteria [66][67][68][69][70][71][72][73][74][75][76], as is the case in this paper as well.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…There is little doubt that AHP has been frequently adopted. Along with its traditional applications, it has also been used lately in conjunction with others methods: data envelopment analysis (DEA) [57], fuzzy sets [58,59], neural networks [60], SWOT-analysis [61] among others.…”
Section: Plos Onementioning
confidence: 99%
“…All multi-criteria techniques are applied to the same initial data from the initial decision-making matrix and with the same values of the criteria weights. Numerous studies showed that the application of different models for data normalization could influence the change of the ranking results [75][76][77][78][79]; thus in this analysis are selected the multi-criteria methods, which apply different ways of data normalization. The results of the application of the mentioned methods are presented in Fig.…”
Section: Comparison Of the Results With Other Multi-criteria Techniquesmentioning
confidence: 99%